Envelope tessellation with stochastic rotation of 4-fold penttiles - Hanafin, Stuart; Datta, Sambit; Rolfe, B.; Hobbs, M. (School of Architecture Hindustan University, 2012)
The challenge of developing adaptive, responsive low-energy architecture requires new knowledge about the complex and dynamic interaction between envelope architecture and optimisation between competing environmental performance metrics. Advances in modelling the geometry of building envelopes and control technologies for adaptive buildings now permit the sophisticated evaluation of alternative envelope configurations for a set of performance criteria. This paper reports on a study of the parametric control of a building envelope based on moveable facade components, acting as a shading device to reduce thermal gain within the building. This is investigated using a novel pentagonal tiling strategy considering the component design, tessellation and control methods.